Patient perspectives on hypertension management in health system of Sri Lanka: a qualitative study - H Asita de Silva; Anuradhani Kasturiratne; Channa D Ranasinha; Tazeen H Jafar; Helena Legido-Quigley; Manuja Perera; Chamini Kanatiwela de Silva; Saeideh Tavajoh; Nathathasa Vihangi Luke (BMJ Open)
Introduction Uncontrolled hypertension is the leading risk factor for mortality globally, including low-income and middle-income countries (LMICs). However, pathways for seeking hypertension care and patients’ experience with the utilisation of health services for hypertension in LMICs are not well understood.Objectives This study aimed to explore patients’ perspectives on different dimensions of accessibility and availability of healthcare for the management of uncontrolled hypertension in Sri Lanka.Setting Primary care in rural areas in Sri Lanka.Participants 20 patients with hypertension were purposively sampled from an ongoing study of Control of Blood Pressure and Risk Attenuation in rural Bangladesh, Pakistan, Sri Lanka.Method We conducted in-depth interviews with patients. Interviews were audio-recorded and transcribed into local language (Sinhala) and translated to English. Thematic analysis was used and patient pathways on their experiences accessing care from government and private clinics are mapped out.Results Overall, most patients alluded to the fact that their hypertension was diagnosed accidentally in an unrelated visit to a healthcare provider and revealed lack of adherence and consuming alternatives as barriers to control hypertension. Referring to the theme ‘Accessibility and availability of hypertension care’, patients complained of distance to the hospitals, long waiting time and shortage of medicine supplies at government clinics as the main barriers to accessing health services. They often resorted to private physicians and paid out of pocket when they experienced acute symptoms attributable to hypertension. Considering the theme ‘Approachability and ability to perceive’, the majority of patients mentioned increasing public awareness, training healthcare professionals for effective communication as areas of improvement. Under the theme ‘Appropriateness and ability to engage’, few patients were aware of the names or purpose of their medications and reportedly missed doses frequently. Reminders from family members were considered a major facilitator to adherence to antihypertensive medications. Patients welcomed the idea of outreach services for hypertension and health education closer to home in the theme ‘Things the patients reported to improve the system’.Conclusion Patients identified several barriers to accessing hypertension care in Sri Lanka. Measures recommended improving hypertension management in Sri Lanka including public education on hypertension, better communication between healthcare professionals and patients, and efforts to improve access and understanding of antihypertensive medications.Trial registration number NCT02657746.